Vitamin D plasma binding protein. Turnover and fate in the rabbit. - Haddad, J G; Fraser, D R; Lawson, D E (The Journal of Clinical Investigation, 1981)
The metabolic disposition of the plasma binding protein (DBP) for vitamin D and its metabolites was studied in adult rabbits. Apo-DBP was purified from rabbit plasma and enzymatically labeled with radioiodine. The radioiodine-labeled protein retained its ability to bind vitamin D sterols and its physicochemical properties. When 125I-labeled DBP and 131I-labeled rabbit albumin were simultaneously injected intravenously, the 125I was cleared from plasma at a faster rate (t 1/2 = 1.7 d) than 131I (t 1/2 = 5 d) and 125I was present in excess of 131I in kidney, liver, skeletal muscle, heart, lung, intestine, testis, and bone 1 h after injection. In contrast to DBP, 25(OH)D3 was cleared more slowly (t 1/2 = 10.7 d). Compared to albumin, DBP radioactivity appeared earlier and in greater quantity in the urine of catheterized rabbits. Gel filtration analyses of plasma revealed most of the 125I to elute in the position of DBP, with only small amounts in the less than 1,000-dalton region. In contrast, almost all of the urine 125I eluted in this small molecular weight fraction. The molar ratio of DBP to 25(OH)D3 in normal rabbit plasma was 138/1. The extravascular pool of DBP was calculated to be 1.5-2.4 times larger than the intravascular DBP pool, and the molar replacement rate of DBP was 1,350-fold higher than that of 25(OH)D3. The plasma disappearance curves of holo-DBP, prepared either by saturating with 25(OH)D3 or by covalently linking 3 beta-bromoacetoxy-25(OH)D3, were very similar to that of apo-DBP. Neuraminidase treatment of DBP did not alter its plasma survival. These studies indicate that DBP or DBP-25(OH)D3 complex is removed from plasma by a variety of tissues, that the DBP moiety is degraded during this process, and that a significant recirculation of 25(OH)D3 probably occurs. The molar excess of DBP to 25(OH)D3 in plasma, and the relatively rapid turnover of DBP indicate that a high capacity, high affinity, and dynamic transport mechanism for vitamin D sterols exists in rabbit plasma. Images